Efficacy and safety of canagliflozin in patients with type 2 diabetes mellitus inadequately controlled with metformin and sulphonylurea: a randomised trial. Issue 12 (13th October 2013) - Wilding, J. P. H.; Charpentier, G.; Hollander, P.; González‐Gálvez, G.; Mathieu, C.; Vercruysse, F.; Usiskin, K.; Law, G.; Black, S.; Canovatchel, W.; Meininger, G.
Summary Aims Canagliflozin is a sodium glucose co‐transporter 2 inhibitor developed for the treatment of type 2 diabetes mellitus (T2DM). This randomised, double‐blind, placebo‐controlled, Phase 3 study evaluated the efficacy and safety of canagliflozin as an add‐on to metformin plus sulphonylurea in patients with T2DM. Methods Patients (N = 469) received canagliflozin 100 or 300 mg or placebo once daily during a 26‐week core period and a 26‐week extension. Prespecified primary end‐point was change in HbA1c at 26 weeks. Secondary end‐points included change in HbA1c at week 52 as well as proportion of patients achieving HbA1c < 7.0%, change in fasting plasma glucose (FPG) and systolic blood pressure, and per cent change in body weight, high‐density lipoprotein cholesterol, and triglycerides (weeks 26 and 52). Results HbA1c was significantly reduced with canagliflozin 100 and 300 mg vs. placebo at week 26 (–0.85%, –1.06%, and –0.13%; p < 0.001); these reductions were maintained at week 52 (–0.74%, –0.96%, and 0.01%). Both canagliflozin doses reduced FPG and body weight vs. placebo at week 26 (p < 0.001) and week 52. Overall adverse event (AE) rates were similar across groups over 52 weeks, with higher rates of genital mycotic infections and osmotic diuresis‐related AEs seen with canagliflozin vs. placebo; these led to few discontinuations. Increased incidence of documented, but not severe, hypoglycaemia episodes was seen with canagliflozin vs. placebo. Conclusions Canagliflozin improved glycaemic control, reduced body weight, and was generally well tolerated in T2DM patients on metformin plus sulphonylurea over 52 weeks.